Effectiveness of Surgical and Non-Surgical Techniques for Accelerating Orthodontic Tooth Movement in Fixed Appliances and Aligners: A Systematic Review - Aline Gonçalves (Turkish Journal of Orthodontics, 2025)
Several procedures have been proposed as adjuvant treatments in orthodontics to accelerate orthodontic tooth movement (OTM). This review aimed to evaluate and compare the effectiveness of surgical and non-surgical techniques in accelerating tooth movement, ascertain the influence of different orthodontic appliances on the rate of tooth movement and analyze their clinical applicability as supportive approaches in orthodontic treatment. A bibliographic search was carried out in April 2024 across Pubmed, Scopus, Web of Science, and the Cochrane Library using combinations of keywords and Medical Subject Heading terms relevant to the topic. The search had no time restriction and was limited to studies published in English. A total of 76 articles were included in this systematic review. Corticotomy exhibited the highest acceleration potential among surgical techniques but is highly invasive and associated with considerable pain and discomfort. Among non-surgical techniques, vibration and photobiomodulation (PBM) showed the most promising results due to their non-invasiveness and effectiveness in accelerating tooth movement. This review provides a comprehensive overview of techniques for accelerating OTM. The literature remains limited in involving surgical and non-surgical procedures using orthodontic aligners, highlighting the need for further research. Considering all the pros and cons, PBM appears to be the most promising technique; however, its effectiveness is yet suboptimal. Future efforts should be dedicated to optimizing PBM protocols to stimulate specific remodeling phenomena, ensuring its establishment as a safe, effective, painless, and non-invasive acceleration technique.